Systematic review of life cycle assessment and life cycle cost analysis for pavement and a case study - Alaloul, W.S. (MDPI AG, 2021)
Development of the pavement network systems, which is inevitable due to the rapid economic growth, has increasingly become a topic of significant concern because of the severe environmental impacts of road expansion. For achieving the sustainable development goals (SDGs), the policies and actions towards the pavementsâ life cycle assessment (LCA) and life cycle cost analysis (LCCA) must be carefully assessed. Consequently, the purpose of this review is to present an overview of LCA and LCCA used in pavement engineering and management. Through the quality control of PRISMA, fiftyâfive most relevant documents were extracted for a thorough investigation. The state of the art review reveals that a limited number of the papers considered environmental impacts of the pavements. Consequently, to assess the environmental impact cost, a conceptual framework was developed to better consider the LCA and LCCA on various aspects of the pavement projects including the sustainability aspects. Besides, a case study was given to validate the literature review towards proposing a novel framework for the incorporation of environmental impact cost. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.